RANCANG BANGUN SISTEM INFORMASI AKADEMIK MAHASISWA BERBASIS WEB PADA “AKBID GRIYA HUSADA” SURABAYA - Saputra, Rizki Aditya; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The midwifery ( akbid ) is an institution of higher education educate of professional in obstetrics. So far all activities in academic manual still in so many problem that happens. Problem that happens when registration among other data noted in the paper thus still missing, krs students takes a long time because the krs still manual. Besides students difficulty know schedule college, values and the presence of because there were no application that presents. There is also an obstacle in the calculation of the value of print and khs since recording value still use microsoft excel.The solution offered was the creation of academic applications which include new student registration process online, ploting class, managing data master, schedule lecture, krs students be done in online, managing data presence, managing data values and yudisium.Designed build the system information academic web-based it may help problems recording data new students, simplify the process krs and scheduling college. Application could also help in knowing schedule lecture and the presence of value. In addition ease the process calculation of the value, print khs and transcript value and produce report of value and graduation students.